Potential uses of perovskite-based photovoltaics for hydrogen production: A pathway to sustainable energy solutions - Kehinde Temitope Alao; Syed Ihtsham ul Haq Gilani; Taiwo Onaopemipo Alao; Abiola Usman Adebanjo; Oluwaseun Ruth Alara (Next Energy)
This review examines the potential of perovskite photovoltaic (PV) cells for clean hydrogen production, a vital component of the global shift toward sustainable energy. Utilizing a systematic review of literature from the Scopus and Web of Science databases, this study provides recent advancements and identifies persistent challenges in the application of perovskite PVs for hydrogen generation. Despite their market dominance, traditional silicon PV cells have limitations that perovskite PVs may overcome. While silicon PV cells achieve efficiencies between 23.3% and 26.7%, lababoratory-scale tandem perovskite PV devices have surpassed this, with efficiencies exceeding 29.8% and a greater potential for future improvement. This efficiency leap positions them as promising candidates for hydrogen production via electrolysis. However, the scalability, stability, and environmental impacts of perovskite PVs necessitate further research in materials science. The review highlights the critical need for advancements in material properties and system integration, as well as supportive policies to foster the adoption of perovskite PVs. Ultimately, the review proposes a strategic framework for optimizing hydrogen production with perovskite-based PV technology, making a significant contribution to the discourse on sustainable hydrogen solutions.